STYLE OF SCIENTIFIC THINKING IN POSTNONCLASSICAL SCIENCE - Скиба, О. П. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article is sanctified to research of features of style of the scientific thinking in modern post-non-classical science